Prosedur Pemeriksaan dalam Hal Penghapusan Nomor Pokok Wajib Pajak Ganda dan Pencabutan Pengusaha Kena Pajak Studi Kasus Kantor Pelayanan Pajak Pratama Pasuruan - Mardliyyah; Irham Maulana, Moh.; Bakhri, Saiful (Teewan Journal Solutions, 2025)
Tax is a primary source of government revenue that supports infrastructure development, social services, and various other government programs. Tax collection and taxpayer compliance are essential for maintaining a country's economic stability. To improve tax efficiency and compliance, the Ministry of Finance of Indonesia introduced the e-filing system, which simplifies the process of filing tax reports electronically, enhances transparency, and reduces human error. Despite the positive impact of this innovation, challenges such as tax literacy and access to technology in some regions remain obstacles. Additionally, improving human resource quality in Indonesia is crucial for enhancing the nation's competitiveness, by providing practical experience for students. This study examines the procedures for eliminating duplicate Taxpayer Identification Numbers (NPWP) and the revocation of Taxable Entrepreneurs (PKP), aimed at improving tax administration efficiency and encouraging taxpayer compliance. The research uses primary data obtained through interviews with taxpayers at the Pratama Tax Service Office in Pasuruan, conducted from September to November 2024. The data collected is qualitative, including detailed descriptions, direct quotes, and case documentation.